Outcomes of Cadaveric Allograft versus Autologous Cartilage Graft in Functional Septorhinoplasty. (November 2019) - Saadi, Robert; Loloi, Justin; Schaefer, Eric; Lighthall, Jessyka G.
Objective: Our goal was to elucidate the efficacy and outcome profile of cadaveric allografts (homograft costal cartilage) in functional septorhinoplasty as compared with autografts (quadrangular cartilage, conchal cartilage, and autologous costal cartilage). Study Design: Retrospective chart review. Setting: Otolaryngology division of the Penn State Health Milton S. Hershey Medical Center. Subjects and Methods: A chart review of a single surgeon's practice was conducted with Current Procedural Terminology codes for septorhinoplasty (30410, 30420, 30430, 30435, 30450, 30465) from August 1, 2014, to August 1, 2017. All patients underwent functional septorhinoplasty for a chief complaint of nasal obstruction. Outcomes were collected up to 12 months following the operation and included the validated Nasal Obstruction Symptom Evaluation (NOSE), infection rate, malposition/warping of the graft, need for revision surgery, and graft loss. Results: A total of 171 cases were included in our data analysis. On multivariate analysis, there were no significant differences between patients who had autografts and those who had allografts in 3-, 6-, or 12-month postoperative NOSE score. Preoperative NOSE score was the only covariate to demonstrate a significant positive relationship to postoperative NOSE score. Regarding outcomes between autograft and allograft, no significant differences were found in rate of graft resorption (3.4% vs 5.6%, P = .680), graft warping (3.4% vs 0%, P = .309), infection (0% vs 1.9%, P = .316), or need for revision surgery (4.3% vs 5.6%, P = .709). Conclusion: Autologous grafting is often the first choice in septorhinoplasty because of its presumed resistance to infection and resorption. Similar to autologous grafts, allografts are resistant to infection and resorption and demonstrate prolonged efficacy following functional septorhinoplasty.